Potential applications of components of aged garlic extract in mitigating pro-inflammatory gene expression linked to human diseases (Review) - Agostinelli, Enzo; Marzaro, Giovanni; Gambari, Roberto; Finotti, Alessia (Experimental and therapeutic medicine, 2025)
In the present review, simple approaches for the screening and characterization of natural compound agents that alter pro-inflammatory gene expression are described, with a particular focus on aged garlic extract (AGE), which has been the subject of several investigations that have supported its potential application as an anti-inflammatory agent. Additionally, evidence regarding the possible effects and mechanisms of action of two major AGE components, S-allyl cysteine (SAC) and S-1-propenyl-l-cysteine (S1PC), is reviewed. The proposed molecular targets of SAC and S1PC are IKKβ kinase, the Kelch-like ECH-associated protein 1-nuclear factor erythroid 2-related factor 2 complex, peroxisome proliferator-activated receptor-γ, histone deacetylase and toll-like receptor 4 (TLR4). Targeting these molecules causes a marked reduction in NF-κB activity accompanied by a notable decrease in the transcription of NF-κB-regulated genes. Another main objective of the present review was to discuss the possibility that AGE and its bioactive components could be employed in the treatment of several human pathologies that are characterized by a hyperinflammatory state resulting from dysregulation of the TLR4 and NF-κB pathways. SAC is of interest in the treatment of lung pathologies, neurological diseases, osteoarthritis, muscular atrophy, cardiovascular diseases, diabetes and cancer. Additionally, the anti-oxidative activities of AGE, SAC and S1PC are compatible with their employment in the treatment of diseases characterized by oxidative stress, such as sickle cell disease and β-thalassemia.